Circular planning and adaptive design strategies to recycle wasted landscapes: The peri-urban territories of Campania Plain as a case-study - Amenta, Libera; Formato, Enrico (International Planning History Society Proceedings, 2016)
The problem of Wasted Landscapes (WL) in the Campania Region is the result of serious social and governmental problems. On one hand, this is a territory in which a large amount of WL is recognisable but, on the other hand it is a porous territory characterised by an adaptive resilience, with great potentialities. Through the last decades, many factors have been overlapping in the complex palimpsest of Campania plain, in the South of Italy. On one hand, the illegal developments and the measures to legitimize them (laws: 1985; 1994; 2003) can be paradoxically understood as real cornerstones for the planning system of this region. On the other hand, the traces of the post-Fordist abandoned landscapes are overlapping with the historical remains, the deep sense of identity and permanence that still persists in the territory of Naples. Today, this problematic condition is mixed with the presence of areas of outstanding natural beauty, with a resilient interstitial agriculture, and with a fragmented but resistant economy. In this paper, two emblematic cases in the Piana Campana are discussed. At a smaller scale, the territory of Casaluce, in the province of Caserta, is an emblematic case of urban dispersion, where the dismantling of urban fabrics, the transformation of agricultural areas in urbanized or polluted territories are interwoven with the illegal spread of new urbanizations and with the loss in attractiveness of the historical centre that is actually becoming increasingly empty. In addition the spatial domain of large infrastructures generates spaces that have no intentional relationships and are not integrated with the city and the territory. Therefore, further action is needed to modernise the under-performing and weak urban metabolism of the City of Casaluce. The studies in support of the new city plan for Casaluce investigate the innovative approach of the circular recycling of Wasted Landscapes in the urban and peri-urban areas. East Naples, the post-industrial part of Naples, had on-going or planned major projects that were developed independently without an overview, as the result of a series of overlapping styles to which infrastructures were added, representing interruptions in the continuity of the area, generating plenty of WL. Through two case studies, the proposed approach shows that in Campania the recycling of WL can represent ways to reactivate urban metabolism, to improve the quality of life, the spatial quality of the territory, and the regional economy. Reversing the way we look at WL means to emphasise the ecological and economical potentialities that they provide for sustainable regeneration of cities and landscapes. In addition, this work understands WL as an additional category of waste with the urgent need to be recycled. The challenge we are talking about needs a new approach to planning and urban-landscape design processes: the paper explores the possibilities coming from the “assemblage thinking” applied in ecological-landscape urbanism, to outline an adaptive and systemic approach. This approach provides a complex cognitive structure, consistent with the reticular and porous contemporary spatial systems.